2010
DOI: 10.1038/ijo.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pain controlling neuropeptides on human fat cell lipolysis

Abstract: Objective: Neuropeptides NPFF and NPSF are involved in pain control, acting through the G-protein coupled receptors (GPR)74 (high affinity for NPFF) and GPR147 (equal affinity for NPFF and NPSF). GPR74 also inhibits catecholamine-induced adipocyte lipolysis and regulates fat mass in humans. The aim of this study was to compare the effects of NPFF and NPSF on noradrenalineinduced lipolysis and to determine the expression of their receptors in human fat cells. Design: Adipose tissue was obtained during surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…NPFF increases AGMO expression through NPFF receptor 2 (NPFFR2) by sustaining IL-4/STAT6 signaling (62). NPFFR2 is the main receptor for NPFF in AT (70,71), and its expression is restricted to ATMs (62). We found that the plasma concentration of NPFF in neonate mice was negligible and increased at weaning ( Figure 7D).…”
Section: Discussionmentioning
confidence: 87%
“…NPFF increases AGMO expression through NPFF receptor 2 (NPFFR2) by sustaining IL-4/STAT6 signaling (62). NPFFR2 is the main receptor for NPFF in AT (70,71), and its expression is restricted to ATMs (62). We found that the plasma concentration of NPFF in neonate mice was negligible and increased at weaning ( Figure 7D).…”
Section: Discussionmentioning
confidence: 87%
“…Appetite control is key in obesity development, and in vitro studies have shown that NPFF inhibits both human and murine adipocyte development (8,9). Peripheral tissues have negligible NPFF receptor expression, with the exception of AT, in which NPFF receptor 2 (NPFFR2, also known as GPR74, HG31, and NPFF2) is expressed (10,11). Genetic variance of NPFFR2 is closely associated with obesity status (12).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variance of NPFFR2 is closely associated with obesity status (12). Human plasma contains NPFF (13), and it is postulated that NPFF may be released from nerve endings in AT (11). However, the in vivo role of NPFF in AT function is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with earlier observations in chicks and rat ( 32 , 43 ) and suggest that GnIH is one of the orexigenic peptide in mammals. An earlier study has demonstrated the presence of RFRP-3 receptor (GPR147) in the adipose tissue ( 44 ). The GnIH containing neurons was shown in contact with the neurons containing neuropeptides, such as neuropeptideY, pro-opio melanocortin, orexin, and melanopeptide, which are known modulators of nutritional changes ( 28 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%